Retirement Confidence: Development of an Index. (27th August 2021) - Ghafoori, Eraj; Mata, Fernanda; Borg, Kim; Smith, Liam; Ralston, Debora
Older workers who are confident about the changes accompanying retirement report higher well-being. We have developed an index to measure retirement confidence – the Retirement Confidence Index (RCI). A six-stage approach was used to develop the index items, including (i) a literature review to catalogue retirement confidence components; (ii) a consultation with a panel of experts to review the proposed indicators and combine components according to their meaning; (iii) normalisation of the selected components to make them comparable; (iv) weighting of the top-level dimensions using experts' judgement; (v) linear aggregation of the dimension scores according to their corresponding relative weight; and (vi) correlation of the composite score with a self-report measure of retirement confidence. Based on the review of the literature, a list of nine sub-components (financial literacy, financial attitude and behaviour, financial control, financial anxiety, physical health, mental health, social connectedness, goal setting for retirement and future uncertainties) was compiled. Subsequently, these components were grouped into four broad dimensions. Correlations between these dimensions (social, financial awareness and skills, health and well-being, and retirement awareness and planning dimensions) and the corresponding self-reported measures were as high as r = 0.555, r = 0.603, r = 0.591 and r = 0.569, reflecting 30.8%, 36.3%, 34.9% and 32.3% shared variance with the corresponding self-reported indices, respectively. The Retirement Confidence Index provides the foundation for future research to measure retirement confidence, with the aim of identifying deficient RCI dimensions and directing efforts to targeted policies to ensure older workers are confident about retirement.